EFEKTIVITAS PENGGUNAAN APLIKASI GOOGLE CLASSROOM PADA PEMBELAJARAN BIOLOGI TERHADAP HASIL BELAJAR SISWA KELAS XI IPA SMA NEGERI 1 TALAGA RAYA - Siti Rahmawati; Wa Ode Asniwia; Ismail (Universitas Cokroaminoto Palopo, 2022)
This study aims to determine the effectiveness of using the google classroom application in improving the learning outcomes of class XI science students at SMA Negeri 1 Talaga Raya. This research is a pre-experimental research using one group pretest-posttest design. The population in this study were students of class XI IPA SMA Negeri 1 Talaga Raya. The sample in this study was class XI IPA 2 which amounted to 30 students. The technique of collecting data is through giving multiple choice tests before (pretest) and after (posttest). The analytical technique used is descriptive analysis and N-Gain test. The results showed that student learning outcomes using the google classroom application increased before and after treatment, from 62.00% to 89.17%. Based on the N-Gain test, student learning outcomes are in the medium (47%) and high (53%). This shows that learning using the google classroom application in biology learning is quite effective in improving the learning outcomes of class XI science students at SMA Negeri 1 Talaga Raya